Critical factors shaping project-based learning in mathematics education - Pham, Chung Xuan; Nguyen, Hang Thi My; Nguyen, Giang Thi Châu; Thai, Lam Thi Hong; Truong, Dung Thi (Institute of Advanced Engineering and Science, 2025)
A total of 488 observations from secondary and high school teachers were randomly divided into two groups for conducting analysis: 244 for exploratory factor analysis (EFA) and 244 for confirmatory factor analysis (CFA). The experimental results from EFA revealed six latent factors, accumulating for over 68.43% of the variance in the data. The CFA reports validated the 6-factor model, demonstrating strong model fit indices and ensuring high reliability and validity. These factors discovered and named in this study are as: facilities and teaching support, capacity to organize project-based learning (PjBL), perception of PjBL, readiness for PjBL, teachers’ confidence in applying PjBL, and students’ characteristics. The findings validated these latent factors’ model as a comprehensive framework for understanding the essential aspects of organizing PjBL. By addressing both the identification and empirical validation of influencing factors, the study thoroughly responds to the research questions and strengthens the overall contribution to the field. This study is novel in its development and validation of a context-specific measurement model for PjBL in mathematics education, particularly within the Vietnamese educational context, where empirically grounded models of this nature remain scarce. Furthermore, it offers valuable practical information for teachers, educational administrators, and researchers to enhance and promote the effective application of PjBL in mathematics education.